The Pengaruh gaya kepemimpinan, budaya kerja, dan motivasi terhadap kinerja karyawan UD. Sekar Makmur Wonoploso Gondang Mojokerto - Mahardika Permana, Thomas; Kridaningsih, Anna; Budiyanto, Fajar (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to analyze the simultaneous, partial, and dominant effects of leadership style, work culture, and motivation on employee performance. The research was conducted at UD. Sekar Makmur, Wonoploso Village, Gondang District, Mojokerto Regency, with a population of 45 employees, sampled using saturation/sensus technique. Data were collected through questionnaires and documentation. The analysis methods employed were descriptive analysis and multiple linear regression. Results indicate significant simultaneous and partial effects of leadership style, work culture, and motivation on employee performance, with work culture exerting the most dominant influence. Recommendations include enhancing work culture, leadership training, motivation stimulation, routine evaluation, and further research for deeper understanding and improved employee performance.